Interaction of EcoRII restriction and modification enzymes with synthetic DNA fragments. V. Study of single-strand cleavages. - Yolov, A A (1985)
Concatemer DNA duplexes which contain at the EcoRII restriction endonuclease cleavage sites (formula; see text) phosphodiester, phosphoamide or pyrophosphate internucleotide bonds have been synthesized. It has been shown that this enzyme did not cleave the substrate at phosphoamide bond. EcoRII endonuclease catalyzes single-strand cleavages both in dA- and dT-containing strands of the recognition site if the cleavage of the other strand has been blocked by modification of scissile bond or if the other strand has been cleaved. This enzyme interacts with both strands of the DNA recognition site, each of them being cleaved independently on the cleavage of another one. Nucleotide sequences flanking the EcoRII site on both sides are necessary for effective cleavage of the substrate.